Synthesis of Pure Nano semiconductor Oxide ZnO with Different AgNO3 Concentrations - Baghdad Science Journal (مجلة بغداد للعلوم)
Zinc oxide nanoparticles sample is prepared by the precipitation method. This method involves using zinc nitrate and urea in aqueous solution, then (AgNO3) Solution with different concentrations is added. The obtained precipitated compound is structurally characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Atomic force microscopy (AFM) and Fourier transform infrared spectroscopy (FTIR). The average particle size of nanoparticles is around 28nm in pure, the average particle size reaches 26nm with adding AgNO3 (0.05g in100ml =0.002 M) (0.1g in100ml=0.0058M), AgNO3 (0.2g in 100ml=0.01M) was 25nm. The FTIR result shows the existence of -CO, -CO2, -OH, and -NO2- groups in sample and oxides (ZnO, Ag2O).and used an atomic force microscope and microscope scanning electron to model the record.